The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4322/rbcv.2015.302
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of zoonoses in freshmen entering the veterinary school

Abstract: In veterinary practice, the risk of zoonotic infections starts in College, when students are exposed to animals, and laboratory assignments. The objective of this study was to estimate awareness of zoonoses in a cohort of freshmen at the Facultad de Ciencias Veterinarias, Universidad Nacional del Litoral, Santa Fe (Argentina). A cross sectional study was conducted using a structured questionnaire in all students attending an introductory course (N= 179) on April, 2012. Data analysis included descriptive statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(9 reference statements)
0
1
0
2
Order By: Relevance
“…This agrees with a study conducted among veterinary students which observed 82% of freshmen knowing the meaning of the word zoonosis. 29 This was a significantly higher figure than that reported in a study in Puducherry, India where only 16.4% of respondents were aware that diseases in animals could be transmitted to people. 30 Also, studies regarding knowledge of zoonosis undertaken in a university in Nigeria contradict the findings of this study as students expressed poor knowledge of zoonosis.…”
Section: Discussionmentioning
confidence: 65%
“…This agrees with a study conducted among veterinary students which observed 82% of freshmen knowing the meaning of the word zoonosis. 29 This was a significantly higher figure than that reported in a study in Puducherry, India where only 16.4% of respondents were aware that diseases in animals could be transmitted to people. 30 Also, studies regarding knowledge of zoonosis undertaken in a university in Nigeria contradict the findings of this study as students expressed poor knowledge of zoonosis.…”
Section: Discussionmentioning
confidence: 65%
“…Aproximadamente cuatro de cada seis estudiantes en Argentina han sufrido estos accidentes durante la revisión clínica de pacientes pero paradójicamente, estas actividades son percibidas como de riesgo medio o bajo por los alumnos (Tarabla et al, 2019). Por otra parte, en un futuro cercano los ingresantes van a estar expuestos a numerosas zoonosis (Sánchez et al, 2017), pero tienen un escaso conocimiento sobre las especies animales susceptibles y las formas de transmisión de estas enfermedades (Molineri et al, 2014). Es probable que las características demográficas de los estudiantes incidan sobre sus motivaciones para estudiar veterinaria y que ellos no estén preparados para enfrentar los peligros ocupacionales a los que se verán expuestos durante el cursado.…”
unclassified
“…En 778 estudiantes de 13 carreras de Veterinaria ubicadas en nueve provincias argentinas la frecuencia de diagnósticos de enfermedades zoonóticas fue del 6% (Tarabla et al, 2019), mientras que la incidencia de casos de zoonosis se eleva notablemente en los primeros años posgraduación (Molineri et al, 2013). Al inicio del cursado los estudiantes tienen un nivel de conocimiento limitado sobre los animales que pueden ser afectados y las formas que estas enfermedades pueden ser trasmitidas al ser humano (Molineri et al, 2014). Las enfermedades más mencionadas por los encuestados fueron: rabia (43,1%), tuberculosis (23,8%), brucelosis (18,5%), toxoplasmosis (15,4%), carbunclo (16,2%), leptospirosis (14,6%), sarna (13,8%) y triquinosis (13,1%).…”
unclassified